Efforts to Utilise Resources to Facilitate Learning in Improving Teacher and Student Performance in Learning Islamic Religious Education Class XI Senior High School 6 Merangin - Muhammad Nuzli; Wiji Handoyo; Gadis Purnama Sari; Irwandi Irwandi (Yayasan Adra Karima Hubbi, 2023)
Background. Education is a conscious and planned effort to create a better human being in the future in the word Islamic language is insan kamil. then in its application, it always makes various kinds of educational innovations so that it can always keep up with the times and can survive in dealing with it. then the use of resources becomes important in this case so that what already exists and can be used as a tool to achieve educational goals can be used and used properly and correctly according to its function. Purpose. The purpose of this study was to evaluate resource utilisation, improve teacher skills, assess organisational effectiveness with the aim of improving teacher and student performance in class XI of state senior high school 6 Merangin. Method. This research uses qualitative research methods. Types and Sources of Data are Primary data and Secondary data. Data Collection Methods with Observation, Interview, Documentation, Techniques and Data Analysis with data reduction, data presentation and conclusion drawing. Results. The results of this research are; 1) Tools, materials, devices, organisations and people related to the field of education at state senior high school 6 Merangin already exist and run only need to be controlled, 2) There are still educators, especially Islamic Religious Education, who are not optimal in using tools, materials, devices as a support for performance improvement, 3) Organisation that is already running should be further improved with good and clear control and communication. Conclusion. The conclusions of this research are; 1) Tools, materials, devices, organisations and people related to the field of education at state senior high school 6 Merangin already exist and run only need to be controlled, 2) There are still educators, especially Islamic Religious Education, who are not optimal in using tools, materials, devices as a support for performance improvement, 3) Organisation that is already running should be further improved with good and clear control and communication.